Persepsi Mahasiswa Terhadap Pembelajaran Online Pada Program Studi Pendidikan Biologi FKIP Universitas Muhammad Yamin Semester Genap 2021/2022 - Chairul Amri Chaniago (Eduscience Development Journal, 2022)
Online learning is an alternative to the learning process carried out during the pandemic or at the time of the new normal era. Online learning has several advantages, including time flexibility where students can follow and do assignments anywhere and anytime. Besides online learning has advantages and conveniences, online learning also has obstacles and obstructions, both from lecturers and students. This study aims to analyze student perceptions of online learning in the biology education study program, FKIP UMMY Solok. This research is a survey research of data collection using a questionnaire as a research instrument. The research sample amounted to 31 people. Research data obtained from data analyzed from questionnaires filled out by students. From the results of the research, it is known that from the aspect of affordability, learning independence, learning effectiveness, equality and communication, the average student has a good perception of online learning in the biology study program of FKIP UMMY Solok.